High-performance rectifiers fabricated on a flexible substrate - Etor, D.; Dodd, L.E.; Wood, D.; Balocco, C. (Applied Physics Letters, 2016)
We report on the fabrication and testing of metal-insulator-metal (MIM) diodes on a flexible substrate where the thin insulating layer self-assembles as a monolayer sandwiched between the two metal electrodes. The current-voltage characteristic has a strong asymmetry and non-linearity at zero-bias. The diodes have a typical zero-bias resistance of 80 kΩ, a zero-bias curvature coefficient of 5.5 V−1, and a voltage responsivity of 3.1 kV/W at a frequency of 1 GHz. The fabrication yield was over 90%, and an encapsulation method to prevent MIM junction degradation has also been developed. The diodes show no significant degradation in performance when the substrate is stressed in a one-off bending experiment, although extensive testing does produce some loss in quality. The fabrication process is simple, cost effective, and carried out at low temperature, opening up the possibility of roll-to-roll volume manufacturing of fast MIM diodes.
EPrint Processing Status: Full text deposited in DRO